Beliefs and instructional practices of pre-service mathematics teachers: a systematic literature review - Alfina Lutfi Rahmawati; Alfiatur Rosida; Anggi Adelia Putri; Anita Zahroh; Annisa Putri Rahmawati; Dwi Nur Cahyo; Syazlin Nadia Mat Radzi (Jurnal Pendidikan Matematika (JPM), 2026)
Pre-service mathematics teachers’ beliefs play a crucial role in shaping instructional practices; however, inconsistencies between beliefs and classroom implementation remain a persistent issue. This study aims to systematically review the literature on pre-service mathematics teachers’ beliefs and examine how these beliefs influence instructional practices. Specifically, it addresses two research questions: “What beliefs are held by pre-service mathematics teachers?” and “How do these beliefs influence their instructional practices?” A systematic literature review approach was employed to ensure a rigorous and transparent synthesis of existing research. Articles were retrieved from the Scopus database, focusing on peer-reviewed journal publications from 2015 to 2026. Using the keyword “beliefs” and applying predefined inclusion and exclusion criteria, 20 articles were selected for qualitative analysis. Data were extracted using a structured framework covering beliefs, instructional practices, and their relationship. The findings reveal three dominant belief categories: traditional, constructivist, and mixed. Instructional practices were categorized as teacher-centered and student-centered. Notably, the results indicate a recurring misalignment between beliefs and practices: pre-service teachers espouse constructivist beliefs yet continue to implement traditional approaches. This study concludes that beliefs alone are insufficient to drive pedagogical change.